A devastação entre mãe e filha e seus destinos trágicos para a mulher. - Alcântara, Elise Dobbin Mendes de (2024)
Devastation is one of the manifestations of the incidence of joy that stands out in the relationship between mother and daughter. As considered by Lacan, the devastation between mother and daughter perceives the daughter's relationship with maternal sexuality in the experience of the Other's enjoyment. In the maternal bond, as Freud highlights, the girl is intertwined with her mother's sexuality and seeks answers to her being a woman. In this work, based on Freud and Lacan, we reflect on women and the tragic effects of devastation between mother and daughter. Clinical listening to the significant concepts of “enjoyment” and “body”, linking them to the devastating destinies in a patient’s life, aroused our interest in problematizing the tragedy in the story of a character, which surprised us by the overwhelming nature of the mother’s joy of imprinting for her daughter a place that collided her desire, which we assume was not a enigma for her daughter. The general objective of the work was to discuss the devastation and tragic fates of a woman in the devastating relationship between mother and daughter. Research was carried out with psychoanalysis, which, starting from fragments of a clinical case and based on the psychoanalytic method of interpretation, proposed a narrative construction and analysis of the story of the character Gypsy Rose, which was referenced in the logic of clinical case construction. The singularity of the series lies in the outings that a character undertook for herself, standing out for the destiny she gave to her body in the face of the instinctual dynamism faced with maternal sexuality, the destiny she traced in the devastation with her mother, in addition to the constitution of a love life with her boyfriend after her maternal death, considering what was tragic in the relationship with the maternal Other.